Digital Technologies for Communication Simulation in Foreign Language Learning under Pandemic - Badan, A. A.; Onishchenko, N.; Zeniakin, O. S. (My University, 2022)
Foreign language acquisition presupposes building up communication skills in audition and speaking by way of using special communicative simulation. With the lack of an authentic foreign language environment it’s important to bring about similar to real-life multimedia simulations that substantially speed up and facilitate language acquisition simultaneously raising the students’ communicative competence. The research offered is the first integrated scientific investigation in the field of multimedia simulation put into practice at the time of a global-scale pandemic. It presents theoretical background of simulations and empirical results achieved during the experiment phase of the research. The paper highlights the use of modern digital tools and their impact on students’ progress. In addition, the authors emphasize the appropriate combination of traditional and multimedia technologies that acquired a special term "blending" in the frame of the student-centered approach.
Keywords: multimedia technologies; communicative simulation; blending; student-centered; educational toolkit